Liposomal Bupivacaine for Pain Control After Anterior Cruciate Ligament Reconstruction: A Prospective, Double-Blinded, Randomized, Positive-Controlled Trial. (July 2016) - Premkumar, Ajay; Samady, Heather; Slone, Harris; Hash, Regina; Karas, Spero; Xerogeanes, John
Background: Local anesthetics are commonly administered into surgical sites as a part of multimodal pain control regimens. Liposomal bupivacaine is a novel formulation of bupivacaine designed for slow diffusion of a single dose of local anesthetic over a 72-hour period. While early results are promising in various settings, no studies have compared pain management regimens containing liposomal bupivacaine to traditional regimens in patients undergoing anterior cruciate ligament (ACL) reconstruction. Purpose: To evaluate liposomal bupivacaine in comparison with 0.25% bupivacaine hydrochloride (HCl) for pain control after ACL reconstruction. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 32 adult patients undergoing primary ACL reconstruction with a soft tissue quadriceps tendon autograft between July 2014 and March 2015 were enrolled. All patients received a femoral nerve block immediately before surgery. Patients then received either a 40-mL suspension of 20 mL Exparel (1 vial of bupivacaine liposome injectable suspension) and 20 mL 0.9% injectable saline or 20 mL 0.5% bupivacaine HCl and 20 mL 0.9% injectable saline, which was administered into the graft harvest site and portal sites during surgery. Patients were given either a postoperative smartphone application or paper-based journal to record data for 1 week after ACL reconstruction. Results: Of the 32 patients recruited, 29 patients were analyzed (90.6%). Two patients were lost to follow-up, and 1 was excluded because of a postoperative hematoma. There were no statistically significant differences in postoperative pain, medication use, pain location, recovery room time, or mobility between the 2 study groups. Conclusion: There were comparable outcomes with 0.25% bupivacaine HCl at a 200-fold lower cost than liposomal bupivacaine. This study does not support the widespread use of liposomal bupivacaine for pain control after ACL reconstruction in the setting of a femoral nerve block. Registration: ClinicalTrials.gov NCT02189317